Safety assessment of Enterococcus lactis based on comparative genomics and phenotypic analysis - Lu, Jingda; Shen, Tingting; Zhang, Yixin; Ma, Xinwei; Xu, Sheng; Awad, Sameh; Du, Muying; Zhong, Zhi (Frontiers in Microbiology, 2023)
Enterococcus (E.) faecium is sometimes used in food production; however, its acquisition of antibiotic resistance has become an alarming health concern. The E. lactis species is closely related to E. faecium and has good probiotic potential. This study aimed to investigate the antibiotic resistance of E. lactis. We analyzed the antibiotic resistance phenotype and whole-genome sequences of 60 E. lactis isolates (23, 29, and eight isolates from dairy products, Koji, and human feces, respectively). These isolates showed varying degree of resistance to 13 antibiotics, and were sensitive to ampicillin and linezolid. The E. lactis genomes carried only a subset of commonly reported antibiotic resistance genes (ARGs) in E. faecium. Five ARGs were detected across the investigated E. lactis, including two universally present genes (msrC and AAC(6')-Ii) and three rarely detected ARGs (tet(L), tetM, and efmA). To identify other undescribed antibiotic resistance-encoding genes, a genome-wide association study was performed, returning 160 potential resistance genes that were associated with six antibiotics, namely chloramphenicol, vancomycin, clindamycin, erythromycin, quinupristin-dalfopristin, and rifampicin. Only around one-third of these genes encode known biological functions, including cellular metabolism, membrane transport, and DNA synthesis. This work identified interesting targets for future study of antibiotic resistance in E. lactis. The fact that the lower number of ARGs present in E. lactis supports that it may be an alternative to E. faecalis for use in the food industry. Data generated in this work is of interest to the dairy industry.